The Effect of the Audiovisual Media-Assisted Demonstration Method on the Independence and Science Learning Outcomes of Fourth Grade Students - Komang Agus Lanang Sugawa; I Gede Astawan; Ni Ketut Desia Tristiantari (Undiksha Press, 2025)
Low learning outcomes and lack of student independence are often attributed to teacher-centered learning. In light of this, it is necessary to implement appropriate learning methods. The demonstration method, which falls under kinesthetic learning, encourages students to think critically. This study aimed to examine the effect of the demonstration method assisted by audiovisual media on student independence and learning outcomes. The population of the study consisted of 138 students. The sample involved two schools: one serving as the experimental group using the audiovisual-assisted demonstration method, and the other as the control group employing conventional learning. The research methods included questionnaires and multiple-choice tests. Data were analyzed using descriptive and inferential statistics (MANOVA test). The results showed a significant effect on learning outcomes (p = 0.000 < 0.05) and student independence (p = 0.000 < 0.05), as well as a simultaneous significance value of 0.000 < 0.05. Therefore, the demonstration method assisted by audiovisual media has a significant positive effect on student independence and learning outcomes. Based on these findings, this method can be considered an effective alternative for improving student independence and academic achievement. This research has implications for schools and teachers to enhance the quality of education by implementing diverse learning methods supported by instructional media that can be adjusted to meet learning needs.